Factors associated with life satisfaction in systemic sclerosis: Examining the moderating roles of social support and spiritual well-being. Issue 2 (June 2023) - Chen, Yen T; Murphy, Susan L; Furst, Daniel E; Clements, Philip; Kafaja, Suzanne; Tsevat, Joel; Malcarne, Vanessa; Khanna, Dinesh
Objectives: Systemic sclerosis often has a significant impact on an individual's quality of life. Life satisfaction is a subjective expression of well-being and a key component of quality of life. We examined the associations between functional limitations, social support, and spiritual well-being with life satisfaction and investigated the moderating roles of social support and spiritual well-being on the relationship between functional limitations and life satisfaction in people with systemic sclerosis. Methods: Data were drawn from the baseline University of California Los Angeles Scleroderma Quality of Life Study. Participants completed questionnaires that included demographics, depressive symptoms, functional limitations, social support, and spiritual well-being. The Satisfaction with Life Scale was used to evaluate overall life satisfaction. Data were analyzed using a hierarchical linear regression. Results: Of 206 participants (84% female, 74% White, 52% limited cutaneous subtype, 51% early disease), 38% reported being dissatisfied with their lives. Functional limitations (β = −0.19, p = 0.006), social support (β = 0.18, p = 0.006), and spiritual well-being (β = 0.40, p < 0.001) were associated with life satisfaction, with spiritual well-being emerging as the strongest statistical contributor. However, social support and spiritual well-being did not significantly moderate the relationship between functional limitations and life satisfaction ( p = 0.882 and p = 0.339, respectively). Conclusion: Spiritual well-being is particularly important in understanding life satisfaction in people with systemic sclerosis. Future longitudinal research is needed to assess and examine spiritual well-being and its impact on life satisfaction in a larger and more diverse systemic sclerosis sample.